"My dad, the deacon:" Assessing the personality of married Catholic clergy fathers as predictor of number and gender of children. Issue 2 (3rd April 2018) - Ferrari, Joseph R.; Guerrero, Mayra
ABSTRACT: Catholic deacons with children ( N  = 1, 776: M number of children = 3.3), termed here "clergy dads, " completed the HEXACO-60, social desirability, and demographic variables. Personality dimensions predicting clergy dad's family size (i.e., number of children) yield only emotional stability and conscientiousness (accounting for social desirability). Higher emotional stability and conscientiousness by clergy dads predicted fewer children in their family size. No personality dimension significantly predicted a child's gender. Results imply that personality traits of clergy dads yield smaller family size but not gender of their children. Implications for the family dynamics of clergy dads are discussed.